TRASH’S TOXIC IMPACT ON OUR ATMOSPHERE - Ramazonova Dinora (European Science Publishing, 2024)
The issue of waste management has long been a significant environmental concern, but its impact on the atmosphere often receives less attention than it deserves. This article explores the toxic effects of trash on our atmosphere, focusing on the emissions from landfills, incineration, and the breakdown of various waste materials. By examining the chemical processes and pollutants involved, this research aims to highlight the urgent need for improved waste management practices and policies to mitigate the atmospheric contamination caused by trash.
Keywords: Waste Management, Atmospheric Pollution, Landfill Emissions, Methane, Volatile Organic Compounds (VOCs), Incineration, Dioxins, Furans, Heavy Metals, Plastic Degradation, Microplastics, Air Quality.